Trust as a Moderator in AI Adoption among Indonesian MSMEs: A Multi-Group Analysis of Necessity versus Opportunity Entrepreneurship - Muhammad Fakhri; Rambat Lupiyoady (Advances in Business & Industrial Marketing Research, 2026)
Purpose: This study aims to examine the moderating role of trust in an extended Unified Theory of Acceptance and Use of Technology (UTAUT) model on artificial intelligence (AI) adoption intention among Indonesian micro, small, and medium enterprises (MSMEs). It also compares the drivers of adoption between necessity-driven and opportunity-driven entrepreneurs. Research Method: This research employed a quantitative cross-sectional survey involving 200 MSME owners in Greater Jakarta selected through purposive sampling. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) and Multi-Group Analysis (MGA) to test direct and moderating effects, and to examine differences between entrepreneurial typologies. Results and Discussion: The findings show that performance expectancy, effort expectancy, and facilitating conditions positively influence AI adoption intention, while personal innovativeness has a significant negative effect, indicating technology intimidation. Trust negatively moderates the effects of performance expectancy and effort expectancy, but positively moderates the effects of facilitating conditions. MGA reveals that performance expectancy and effort expectancy are significant only among opportunity-driven enterprises, whereas facilitating conditions are significant only among necessity-driven enterprises. The model explains 43% of the variance in adoption intention with good predictive relevance. Implications: Policymakers and platform providers should tailor AI adoption strategies by emphasizing efficiency and capability for opportunity-driven MSMEs, while prioritizing infrastructure and support for necessity-driven MSMEs. Originality: This study highlights entrepreneurial typology and trust as contextual factors in AI adoption among Indonesian MSMEs.